RETRACTED: Energy Efficiency in the Post-COVID-19 Era: Exploring the Determinants of Energy-Saving Intentions and Behaviors - Bilal Ahmad; Bilal Ahmad; Muhammad Irfan; Muhammad Irfan; Muhammad Irfan; Sultan Salem; Mirza Huzaifa Asif (Frontiers in Energy Research)
The COVID-19 pandemic has a long-lasting influence on global economies. Households are expected to consume more electricity for their usual routine activities due to mandatory stay-at-home restrictions, resulting in greater energy utilization. The proposed study seeks to investigate the most relevant energy consumption factors amid the COVID-19 pandemic. The study employs a structural equation modeling approach to evaluate the responses from 511 Pakistani residents. Empirical results report a positive and significant association among perceived behavioral control (PBC), perceived environmental concern (PEC), perceived monitory benefits (PMB), and intention to save energy (ISE). Positive anticipated emotions (PAE) is found to be a significant predictor of ISE and energy-saving behavior (ESB). As a step further, we extend the analysis to find the moderating effect of perceived COVID-19 disruptiveness (PCD) between the relationship of ISE and ESB. Results reveal that PCD positively moderates this relationship. Based on research findings, policy implications and future research directions are provided for practitioners, researchers, and academicians to fulfill the country’s energy needs on its way to a future of sustainable development.